Production method for co-production of cement by desulfurization of ardealite

Through the reduction and decomposition of phosphogypsum and the mixed grinding of gradient gel materials, combined with composite auxiliary materials, the problems of low early strength and long settling time caused by impurities caused by impurities are solved, and the performance of phosphogypsum cement is improved efficiently. and resource recycling.

CN119118549APending Publication Date: 2024-12-13CHENGDU QIANLIJIN TECHCAL INNOVATION CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411106979.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-13
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Due to differences in impurity composition and content, phosphogypsum cement clinker has low strength and long settling time, and it is difficult for existing methods to effectively improve the lack of performance through added reagents.

Method used

After reducing and decomposing phosphogypsum, the silicate, ferroalaluminate and phosphate content are determined, and the gradient content of gel materials are added for mixing and grinding, combining composite auxiliary materials such as fly ash, electrolytic aluminum slag and nanomontmorillonite. Prepare phosphogypsum cement with higher strength and shorter settling time in the early stage.

Benefits of technology

It improves the overall usage performance of phosphogypsum cement, reduces production costs, improves production efficiency, and effectively eliminates the environmental protection problems of phosphogypsum stacking and treatment, and promotes the recycling of phosphogypsum resources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004991106500000061
    Figure BDA0004991106500000061
  • Figure BDA0004991106500000062
    Figure BDA0004991106500000062
  • Figure BDA0004991106500000071
    Figure BDA0004991106500000071
Patent Text Reader

Abstract

The invention relates to the technical field of gypsum, and discloses a production method for ardealite desulfurization and co-production of cement, which comprises the following steps: S1, carrying out reductive decomposition on ardealite to obtain ardealite clinker, and measuring the contents of silicate, aluminoferrite and phosphate in the ardealite; s2, dividing the ardealite clinker into a plurality of equal parts according to the content measured in the step S1, sequentially adding a gel material with gradient content into each part of ardealite clinker, and uniformly mixing to obtain a mixture; s3, grinding and sieving each part of the mixed material; and mixing a plurality of parts of mixed materials, and adding composite auxiliary materials to obtain the phosphogypsum cement. According to the invention, special phase clinker which is generated by decomposing phosphogypsum and contains a mixture of calcium silicate, calcium aluminoferrite, calcium phosphate, a small amount of sulfur-containing compounds and the like is subjected to compatibility, and components such as a gel material and the like are added for mixing, grinding and the like according to special impurity components in the phosphogypsum and the content of the special impurity components in the phosphogypsum; the problems of low early strength, long setting time and the like of the phosphogypsum cement clinker due to impurities can be effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of gypsum, and in particular to a production method for desulfurizing phosphogypsum and co-producing cement. Background Art

[0002] Phosphogypsum is a solid waste produced in the wet phosphoric acid process. Its main component is the precipitation and crystallization of calcium sulfate dihydrate produced by the double decomposition reaction of phosphate rock and sulfuric acid. The main reaction process is as follows:

[0003] Ca 5 F(PO 4 ) 5 +H 2 SO 4 +10H 2 O → 3H 3 PO 4 +5CaSO 4 ·2H 2 O↓+HF↑ (1).

[0004] Phosphogypsum is an industrial solid by-product that has to be produced in current industrial production, and the total amount is huge. During the stacking process, it will transfer a large amount of soluble phosphorus and fluorine to the environment through water bodies, thereby causing pollution of soil, water systems, and atmosphere. Therefore, how to utilize phosphogypsum has become a widely concerned issue. At present, phosphogypsum is mostly used directly in building materials, such as gypsum boards, gypsum blocks, gypsum putty, etc. However, compared with natural gypsum or desulfurized gypsum, phosphogypsum is limited by the previous process and has problems such as easy production of salt frost or mildew, low specific surface area, and unstable reaction activity. Therefore, it is necessary to produce sulfuric acid and cement according to the principles of reduction, recycling and reuse of the calcium and sulfur elements in the phosphogypsum in a circular economy to achieve efficient utilization of phosphogypsum. The above processing process mainly involves the following chemical reactions:

[0005] CaSO 4 +2C=CaS+2CO 2 ↑ (2);

[0006] 3CaSO 4 +CaS=4CaO+4SO 2 ↑ (3);

[0007] 2CaO+SiO 2 =2CaO·SiO 2 (4);

[0008] 3CaO+SiO 2 =3CaO·SiO 2 (5);

[0009] 3CaO+Al2 O 3 =3CaO·Al 2 O 3 (6);

[0010] 3CaO+Fe 2 O 3 =3CaO·Fe 2 O 3 (7);

[0011] CaSO 4 +3CaS=4CaO+4S (8);

[0012] C+O 2 =CO 2 ↑ (9);

[0013] S+O 2 =SO 2 ↑ (10);

[0014] 3CaO+3H 3 PO 4 =Ca 3 (PO 4 ) 2 +3H 2 O (11);

[0015] CaO+2CaHPO 4 =Ca 3 (PO 4 ) 2 +H 2 O (12);

[0016] Among them, reactions (2) and (3) are reduction and decomposition reactions of phosphogypsum, and reactions (4) to (7) are mineralization and burning reactions involved in cement production. They are all major reactions in the processing process and are affected by many factors, such as the calcium and silicon content ratio of the reactants, the particles and temperature of silicon oxide, and the iron and aluminum element composition content. Reactions (8) to (12) are side reactions in the processing process and involve reactions of phosphorus impurities. The above reaction processes jointly determine the difficulty and practical economy of production.

[0017] Phosphogypsum is derived from the wet phosphoric acid process. It contains phosphorus and other elements, which always affect the subsequent production of cement and sulfuric acid. This is an inevitable fact. Due to the difference in the special impurity components and content in phosphogypsum, the mineral composition of the processed cement clinker has a special phase. Compared with the cement clinker produced by limestone used in conventional cement, the product performance is significantly different, and the existing phosphogypsum cement clinker has always been difficult to overcome the performance deficiencies caused by impurities. Summary of the invention

[0018] The technical problems to be solved by the present invention are:

[0019] Since phosphogypsum is a solid waste generated in the wet phosphoric acid process, it inevitably contains multi-component impurities. The special composition and content of these impurities have a significant impact on the performance of subsequent phosphogypsum cement clinker, etc., specifically, there are deficiencies such as low early strength and long setting time. These effects caused by the defects of phosphogypsum itself are difficult to be well improved by subsequent external reagents, that is, the performance deficiencies of phosphogypsum cement clinker caused by impurities have not been well resolved.

[0020] The technical solution adopted by the present invention is:

[0021] The present invention provides a method for producing phosphogypsum desulfurization and cement, comprising the following steps:

[0022] S1 reduces and decomposes the phosphogypsum to obtain phosphogypsum clinker, and determines the contents of silicate, aluminaferrite and phosphate in the phosphogypsum;

[0023] S2: dividing the phosphogypsum clinker into a plurality of equal portions according to the content determined in step S1, and sequentially adding a gel material with a gradient content to each portion of the phosphogypsum clinker, mixing them evenly, to obtain a mixed material;

[0024] S3: grinding and sieving each portion of the mixed material; then mixing multiple portions of the mixed material, adding composite auxiliary materials, and obtaining the phosphogypsum cement.

[0025] Preferably, in step S2, the amount of gel material added is 0-60wt% of the mass of the phosphogypsum clinker.

[0026] Preferably, in step S2, the gel material may be one or more of 32.5R cement, 42.5R cement and 52.5R cement.

[0027] Preferably, when the gel material is 32.5R cement, the amount of the gel material added is 30-50wt% of the mass of the phosphogypsum clinker;

[0028] When the gel material is 42.5R cement, the amount of gel material added is 20-40wt% of the mass of phosphogypsum clinker;

[0029] When the gel material is 52.5R cement, the addition amount of the gel material is 10-30wt% of the mass of the phosphogypsum clinker.

[0030] Preferably, in step S3, the grinding fineness is 30-60 μm, and the sieve residue after grinding is ≤5wt%.

[0031] Preferably, the specific surface area of ​​the ground powder is 300-400m2 / kg.

[0032] Preferably, the composite auxiliary materials include 1.2-3wt% fly ash, 2.5-8wt% electrolytic aluminum slag and 3-10wt% nano-montmorillonite.

[0033] Preferably, the preparation method of the nano-montmorillonite comprises the following steps:

[0034] The crushed montmorillonite and the silane coupling agent are mixed evenly, placed at 80±5° C., stirred for reaction for 8±2 hours, and then washed with ethanol to obtain the nano-montmorillonite.

[0035] Preferably, the particle size of the nano-montmorillonite is 30±5 nm.

[0036] The beneficial effects of the present invention are as follows:

[0037] According to the differentiation and leveling effect, the present invention mixes the special phase clinker containing calcium silicate salt, calcium aluminoferrate salt, calcium phosphate and a small amount of sulfur-containing compounds produced by the decomposition of phosphogypsum, and according to the special impurity components and their contents in the phosphogypsum, adds components such as gel materials for mixing and grinding, so as to prepare phosphogypsum cement with higher early strength and shorter setting time, improves the overall use performance of the phosphogypsum cement, has low production cost and high production efficiency, eliminates the environmental protection problem of phosphogypsum stacking treatment, can effectively consume solid waste phosphogypsum on a large scale, and improves the recycling path and effect of phosphogypsum resources. DETAILED DESCRIPTION

[0038] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0039] The present invention provides a production method of phosphogypsum desulfurization and co-production of cement, wherein a special phase clinker containing a mixture of calcium silicate salt, calcium aluminoferrate, calcium phosphate and a small amount of sulfur-containing compounds produced by decomposing phosphogypsum is mixed, and gel materials and other components are added according to the special impurity components and their contents in the phosphogypsum for mixing and grinding, so as to prepare phosphogypsum cement with higher early strength and shorter setting time, thereby improving the overall use performance of the phosphogypsum cement, and having low production cost and high production efficiency, eliminating the environmental protection problem of phosphogypsum stacking and treatment.

[0040] The specific production method is as follows:

[0041] (1) First, the clinker obtained by reduction and decomposition of phosphogypsum is tested to determine the contents of silicate, aluminaferrite, phosphate and other components therein.

[0042] (2) According to the content of each component in the phosphogypsum clinker, the phosphogypsum clinker is divided into multiple equal portions, and a gradient content of gel material is added to each portion of the phosphogypsum clinker, and each portion is mixed evenly.

[0043] Among them, the mass of the gel material accounts for 0-60wt% of the mass of the phosphogypsum clinker; the gel material can be selected from 32.5R cement, 42.5R cement and 52.5R cement. When the gel material is 32.5R limestone cement, its addition amount is preferably 30-50wt%, when the gel material is 42.5R limestone cement, its addition amount is preferably 20-40wt%, when the gel material is 52.5R limestone cement, its addition amount is preferably 10-30wt%.

[0044] (3) Grind each portion of the mixed clinker to a fineness of 30-60 μm until the sieve residue does not exceed 5 wt%. The specific surface area of ​​the ground powder is about 300-400 m 2 / kg, then mix each portion of clinker according to the amount, add composite auxiliary materials and common base materials such as sand and gravel to obtain phosphogypsum cement.

[0045] In the present invention, the composite auxiliary material includes 1.2-3wt% of fly ash, 2.5-8wt% of electrolytic aluminum slag and 3-10wt% of nano-montmorillonite, and the nano-montmorillonite is obtained by mixing crushed montmorillonite with a silane coupling agent, stirring at about 80±5°C for about 10 hours, and then washing with ethanol to obtain a high specific surface area nano-montmorillonite with a particle size of about 30±5nm.

[0046] Example 1

[0047] The composition and content of the phosphogypsum clinker obtained by reduction and decomposition of phosphogypsum are shown in Table 1 below:

[0048] Table 1 Composition and content of cement clinker

[0049] Composition CaO <![CDATA[SiO 2 ]]> <![CDATA[Al 2 THE 3 ]]> <![CDATA[Fe 2 THE 3 ]]> MgO <![CDATA[SO 3 ]]> <![CDATA[P 2 THE 5 ]]> content(%) 63.18 25.60 3.92 2.90 0.92 1.56 2.25 Composition F S Cl <![CDATA[C 3 S]]> <![CDATA[C 2 S]]> <![CDATA[C 3 A]]> <![CDATA[C 4 OF]]> content(%) 0.01 0.02 0.001 27.18 49.07 5.33 6.69

[0050] The above-mentioned phosphogypsum clinker is divided into five portions, and 0, 10wt%, 20wt%, 30wt% and 40wt% of 42.5R limestone cement are added to each portion of the phosphogypsum clinker in turn, and the mixed materials are marked as material A, material B, material C, material D and material E.

[0051] Grind the above five materials separately with a grinder, with a grinding fineness of 45μm, until the sieve residue is less than 5wt%. Take 450±2g of each material, add 1350±5g of sand and 225±1g of water, stir and mix, and test the strength of each material at different times according to the GB / T 17671-2021 cement mortar strength test method. The results are summarized in Table 2:

[0052] Table 2 Strength test results of different materials

[0053]

[0054] Among them, as the proportion of 42.5R limestone cement increases, the material strength increases accordingly, which is due to the enhancement effect of the physical complementation brought about by the interaction. The above materials are mixed in equal amounts and stirred evenly to obtain phosphogypsum cement.

[0055] It has been measured that the compressive strength of phosphogypsum cement is 27.0MPa (3d) and 55.3MPa (28d), and the flexural strength is 5.6MPa (3d) and 7.6MPa (28d), which can meet the cement strength requirements of different age periods, such as early and late stages.

[0056] Example 2

[0057] The composition and content of the phosphogypsum clinker obtained by reduction and decomposition of phosphogypsum are shown in Table 3 below:

[0058] Table 3 Composition and content of cement clinker

[0059]

[0060]

[0061] The above-mentioned phosphogypsum clinker is divided into three portions, and 30wt% 32.5R limestone cement, 30wt% 42.5R limestone cement and 30wt% 52.5R limestone cement are added to each portion of the phosphogypsum clinker in turn, and the mixed materials are marked as material A, material B and material C.

[0062] Grind the above three materials separately with a grinder, with a grinding fineness of 45μm, until the sieve residue is less than 5wt%. Take 450±2g of each material, add 1350±5g of sand and 225±1g of water, stir and mix, and test the strength of each material at different times according to the GB / T 17671-2021 cement mortar strength test method. The results are summarized in Table 4:

[0063] Table 4 Strength test results of different materials

[0064]

[0065] As can be seen from the above table, different types of limestone cement will also directly affect the strength of the material. The above materials are mixed in equal amounts and stirred evenly to obtain phosphogypsum cement.

[0066] It has been measured that the compressive strength of phosphogypsum cement is 28.2MPa (3d) and 55.9MPa (28d), and the flexural strength is 5.5MPa (3d) and 7.8MPa (28d), which can meet the cement strength requirements of different age periods, such as early and late stages.

[0067] Example 3

[0068] The composition and content of the phosphogypsum clinker obtained by reduction and decomposition of phosphogypsum are shown in Table 5 below:

[0069] Table 5 Composition and content of cement clinker

[0070]

[0071]

[0072] The above-mentioned phosphogypsum clinker is divided into four portions, and 30wt% 42.5R limestone cement, 40wt% 42.5R limestone cement, 20wt% 52.5R limestone cement and 30wt% 52.5R limestone cement are added to each portion of the phosphogypsum clinker in turn, and the mixed materials are marked as material A, material B, material C and material D.

[0073] The above four materials were ground separately with a grinder, with a grinding fineness of 45μm, until the sieve residue was less than 4wt%. Take 450±2g of each material, add 1350±5g of sand and 225±1g of water, stir and mix, and test the strength of each material at different times according to the GB / T 17671-2021 cement mortar strength test method. The results are summarized in Table 6:

[0074] Table 6 Strength test results of different materials

[0075]

[0076] Subsequently, the above materials are mixed in equal amounts and stirred evenly to obtain phosphogypsum cement.

[0077] It has been measured that the compressive strength of phosphogypsum cement is 28.4MPa (3d) and 55.9MPa (28d), and the flexural strength is 5.8MPa (3d) and 7.7MPa (28d), which can meet the cement strength requirements of different age periods, such as early and late stages.

[0078] According to the requirements for cement clinker strength in GB / T175-2023 "General Portland Cement", the performance of the phosphogypsum cement in the above Examples 1 to 3 is compared as shown in Table 7 below.

[0079] Table 7 Strength requirements at different ages in GB175-2023 general purpose Portland cement

[0080]

[0081] By comparing the strength test results of material A, material B, material C, material D, material E and phosphogypsum cement at different ages in Examples 1 to 3 with the cement strength requirements in the above-mentioned GB / T175-2023 "General Portland Cement", it can be found that: the production method of phosphogypsum desulfurization and co-production of cement adopted in the present invention can achieve a higher level of strength at different periods, and the strength of phosphogypsum cement is improved on the strength of base materials such as material A. This shows that the above-mentioned composite preparation method can effectively improve the problem of low early strength of phosphogypsum cement, so that the overall strength of phosphogypsum cement at different ages can be maintained at a high level.

[0082] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for producing cement by desulfurization of phosphogypsum, characterized in that: The steps include: S1 reduces and decomposes the phosphogypsum to obtain phosphogypsum clinker, and determines the contents of silicate, aluminaferrite and phosphate in the phosphogypsum; S2: dividing the phosphogypsum clinker into a plurality of equal portions according to the content determined in step S1, and sequentially adding a gel material with a gradient content to each portion of the phosphogypsum clinker, mixing them evenly, to obtain a mixed material; S3: grinding and sieving each portion of the mixed material; then mixing multiple portions of the mixed material, adding composite auxiliary materials, and obtaining the phosphogypsum cement.

2. The method for producing phosphogypsum desulfurization and cement according to claim 1, characterized in that: In step S2, the amount of gel material added is 0-60wt% of the mass of phosphogypsum clinker.

3. The method for producing phosphogypsum desulfurization and cement according to claim 1, characterized in that: In step S2, the gel material may be one or more of 32.5R cement, 42.5R cement and 52.5R cement.

4. The method for producing phosphogypsum desulfurization and cement according to claim 3, characterized in that: When the gel material is 32.5R cement, the amount of gel material added is 30-50wt% of the mass of phosphogypsum clinker; When the gel material is 42.5R cement, the amount of gel material added is 20-40wt% of the mass of phosphogypsum clinker; When the gel material is 52.5R cement, the addition amount of the gel material is 10-30wt% of the mass of the phosphogypsum clinker.

5. The method for producing phosphogypsum desulfurization and cement according to claim 1, characterized in that: In step S3, the grinding fineness is 30-60 μm, and the sieve residue after grinding is ≤5wt%.

6. The method for producing phosphogypsum desulfurization and cement according to claim 5, characterized in that: The specific surface area of ​​the ground powder is 300-400m 2 / kg.

7. The method for producing cement by desulfurization of phosphogypsum according to any one of claims 1 to 6, characterized in that: The composite auxiliary materials include 1.2-3wt% of fly ash, 2.5-8wt% of electrolytic aluminum slag and 3-10wt% of nano-montmorillonite.

8. The method for producing phosphogypsum desulfurization and cement according to claim 7, characterized in that: The preparation method of the nano-montmorillonite comprises the following steps: The crushed montmorillonite and the silane coupling agent are mixed evenly, placed at 80±5° C., stirred for reaction for 8±2 hours, and then washed with ethanol to obtain the nano-montmorillonite.

9. The method for producing phosphogypsum desulfurization and cement according to claim 8, characterized in that: The particle size of the nano-montmorillonite is 30±5 nm.

10. A phosphogypsum cement prepared by the production method according to any one of claims 1 to 9.